2006
DOI: 10.1039/b516130d
|View full text |Cite
|
Sign up to set email alerts
|

A general one-pot synthesis for elusive 2-substituted indenes: does bis[2-(tert-butyl)indenyl]zirconium(iv) dichloride/MAO polymerise ethene?

Abstract: Among the 2-substituted indenes, 2-trifluoroindene and 2-tert-butylindene are poorly or incompletely described in the open literature. We herein describe an efficient one-pot synthesis of these compounds as a variation of the Perkin reaction which allows us to refute an earlier claim that bis(2-tert-butylindenyl)zirconium(IV) dichloride (2a) will not polymerise ethene. In fact, 2a/MAO polymerises ethene to extremely high molecular weights. Extensive DFT calculations on the polymerisation mechanism revealed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…This finding is supported by experimental polymerization results, which clearly favor BHE termination products over BHT products for 2 . This is in agreement with our earlier studies on the carbon analogue of 2 , bis(2- tert -butylindenyl)zirconium(IV) dichloride, that does not feature chain termination by BHT at all due to steric congestion …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is supported by experimental polymerization results, which clearly favor BHE termination products over BHT products for 2 . This is in agreement with our earlier studies on the carbon analogue of 2 , bis(2- tert -butylindenyl)zirconium(IV) dichloride, that does not feature chain termination by BHT at all due to steric congestion …”
Section: Discussionsupporting
confidence: 93%
“…The molecular weights decreased with increasing temperature, as it is expected from theory because the termination reactions are subjected to activation barriers. The activation barrier for propagation is usually low if existent at all, and an increase in temperature is therefore not expected to affect the overall enchainment rate as strongly as it does the termination rate. In other words, enchainment is governed by a large exponential term, that is, association rate limit of monomer into the co-ordination sphere (bimolecular process), whereas for termination the exponential term is still growing and association rate of monomer is not relevant (unimolecular process).…”
Section: Experimental Investigationmentioning
confidence: 99%
“…GPC analysis of the polyethylenes produced with benzothiazole based complexes revealed that the symmetric catalysts systems were capable to produce resins with very high molecular weights [28,29] associated with broad or even bimodal molecular weight distributions (Fig. 13).…”
Section: Polymerization Resultsmentioning
confidence: 98%
“…Isoprene was dried over trioctylaluminum and distilled prior to use. Homoleptic Ln­(AlMe 4 ) 3 (Ln = La, Lu), HInd Si , and HInd t Bu , , as well as Li­(Ind), Li­(Ind Et ), Li­(Ind Si ), and Li­(Ind t Bu ), were prepared according to literature procedures . NMR spectra were recorded on a Bruker AVBII+400 ( 1 H: 400.11 MHz; 13 C: 100.61 MHz) spectrometer.…”
Section: Methodsmentioning
confidence: 99%